Optimalisasi Kompetensi Bidan Melalui Workshop Deteksi Dini Dan Upaya Preventif Preeklampsia di Lombok Timur - Astika Gita Ningrum; Dewi Setyowati; Zamrotul Izzah; Andriyanti; Farah Diba Azzahra; Misheel Trivena Setiawan (STMIK Royal, 2025)
Abstract: Preeclampsia is one of the leading causes of maternal mortality in East Lombok Regency. In 2023, 2,689 cases of preeclampsia were recorded among 108,035 pregnant women. Limited competence of midwives in early detection, midwifery care, and preventive strategies remains a major challenge. This community service program aimed to improve midwives’ knowledge and skills through a workshop consisting of seminars and case-based learning (CBL). The activity was conducted on August 25, 2025, at the East Lombok District Health Office Hall, involving 35 midwives from 35 primary health centers (34 respondents were analyzed as one participant did not complete the pre- and post-tests). The workshop covered preeclampsia screening, midwifery care, MgSO₄ administration, and the use of local natural resources as preventive strategies. Evaluation using pre- and post-tests showed a significant increase in the mean score from 78.23 to 94.85, with an average improvement of 16.62 points. Notably, 44.1% of participants achieved a perfect score of 100. These findings confirm that interactive and practical workshop approaches effectively enhance midwives’ competencies. Therefore, this program contributes to strengthening primary health care services and supporting maternal mortality reduction efforts in East Lombok. Keywords: early detection; maternal mortality; midwives competence; preeclampsia; primary health care Abstrak: Preeklampsia merupakan salah satu penyebab utama tingginya angka kematian ibu di Kabupaten Lombok Timur. Data tahun 2023 menunjukkan terdapat 2.689 kasus preeklampsia dari 108.035 ibu hamil. Keterbatasan kompetensi bidan dalam deteksi dini, asuhan kebidanan, dan pemanfaatan strategi preventif menjadi tantangan utama. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pengetahuan dan keterampilan bidan melalui workshop yang terdiri dari seminar dan praktik berbasis kasus (Case Based Learning/CBL). Kegiatan dilaksanakan pada 25 Agustus 2025 di Aula Dinas Kesehatan Lombok Timur, dengan peserta 35 bidan dari 35 Puskesmas. Materi workshop mencakup skrining preeklampsia, asuhan kebidanan, pemberian MgSO₄, serta pemanfaatan bahan alam lokal sebagai strategi preventif. Evaluasi menggunakan pre-test dan post-test menunjukkan peningkatan signifikan skor rata-rata dari 78,23 menjadi 94,85, dengan rata-rata peningkatan sebesar 16,62 poin. Sebanyak 44,1% peserta mencapai skor sempurna 100. Hasil ini membuktikan bahwa workshop interaktif dan aplikatif efektif meningkatkan kompetensi bidan. Dengan demikian, program ini berkontribusi pada penguatan layanan primer dan upaya penurunan angka kematian ibu di Lombok Timur. Kata kunci: angka kematian ibu; deteksi dini; kompetensi bidan; pelayanan kesehatan primer; preeclampsia